Editorial - Chacón Alvarado, Lucía (2002)
This volume of the Bulletin LIBRARIES and the next intended as a means of inspiration. Inspiration to propose ideas to offer to the community library paths to adapt to global culture and technology which revolves around the progress of information and communication systems. Ideas that move us to innovate, to make mistakes and correct them.Because the information age it is also of creativity. Creativity is the competitive advantage of professional and modern organizations. Ideas to change attitudes toward open to new projects that facilitate the transformation and to the challenge of "going global". Inspiration to measure and produce constructive thinking to help us define new goals by the desire to create and share knowledge.